(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Asthma is considered as disease of childhood but may continue in elderly or elderly may be diagnosed as asthmatic for the fi rst time. Asthma in elderly may differ from young with respect to diagnosis and management on account of psychosocial and economic differences and age related changes which may further be enhanced because of comorbidities and interactions between the drugs used for comorbidities. Methodology: Young and elderly asthmatics were compared with regards to Symptoms, Severity (Global Initiative for Asthma: GINA guidelines), Accessibility to treatment, Co-morbidities, Inhalational techniques, Compliance and factors affecting compliance and; Outcome measures. These patients were followed up periodically for above said parameters. Results: Salient differences noted in elderly vs young were: higher GINA scoring (Moderate Persistent: 30% vs 10%), baseline non-compliance (60% vs 30%), non-compliance due to cost and memory (80% vs 26.7%), incorrect technique of inhalation (69.6% vs 42.4%), comorbidities (98% vs 38%) and concomitant drug usage (68% vs 40%). There were differences in symptoms and quality of life indicators. There was signifi cant improvement in various parameters in both groups, especially the young if counseled properly. Conclusion: Signifi cant differences exist between elderly and young asthmatics. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 19-25 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6961